The slope is -1. 3x+3y=12 Subtract 3x 3y=-3x+12 Divide by 3 y=-x+4
y equals 3x has the greater slope.
2x + 3y = 17 3x + 4y = 24 (2x + 3x) + (3y + 4y) = (17 + 24) 5x + 7y = 41
Multiply first equation by 1.5, giving 3x + 3y = 12, but we are told that 3x + 3y = 6. If there isn't an error in the question then 2 = 1!
70000000y=35t
no, 4x-3y=11x 3x-5y doesn't equal -11
The slope is -1. 3x+3y=12 Subtract 3x 3y=-3x+12 Divide by 3 y=-x+4
2x+3y=13 3x-y=3 x=2
9xy
y equals 3x has the greater slope.
2x + 3y = 17 3x + 4y = 24 (2x + 3x) + (3y + 4y) = (17 + 24) 5x + 7y = 41
It is a straight line equation that can be simplified to: y = 3x-9
Multiply first equation by 1.5, giving 3x + 3y = 12, but we are told that 3x + 3y = 6. If there isn't an error in the question then 2 = 1!
70000000y=35t
-3x - 9 = 3y -x - 3 = y y = -(x+3)
(0,-4)
x = 2.15 and y = 3.75